v.1 - Singh, Har Mohinder (ed.); Kaushik, K. C. (ed.); Sharma, S.R. (ed.) (New Delhi Sarup & Sons, 2008)
The Dalits constitute about 30% of one billion population of India and as such they deserve all political, social and economic considerations for their all round development.? In the ancient period the Hindu society had been holding the Dalits which were called by may names such as Sudras, Neech, or Dalit in high esteem and they have held that prophet RAMA honoured Sabri, a tribal lady by visiting her cottage and eating her mouthed berried and that Maharishi Balmiki wrote Sanskrit Ramayana and gave shelter to the two sons ad wife Sita of Lord Rama.? The Main cause of the depression of this important section of Indian society has been ownership of land by the dominant sections of the society.? The Muslim rulers had adopted the system of awarding land to Nawabs, Zagirdars and Thekedars according to their personal considerations.? Since in the feudal age the agricultural system was the main economic occupation, there who owned the land, they were dominant sections of the society.? The Jat in Haryana, the Sikhs in Punjab, the Rajput in Uttar Pradesh and Madhya Pradesh, the Reddies in Andhra Pradesh and the Marathas in Maharastra, had land in their possession and so they were in a dominant position and not only exploited the weaker position of the depressed classes now called the Dalits but they also encouraged feudal practices and traditions.? The artisans like carpenters, blacksmiths, weavers and cobbler were treated as menials.? These sections depended on the agriculturists as they gave them corn in exchange for their service.? Thus they became dependent on these dominant classes for their livelihood.? Ever since India became free from the British rule, the Indian government had taken up the welfare of the Dalits very seriously.? Constitutional provisions have been made for the social, political and economic development of the Dalits.
Volume-1, Raja Ram Mohan Roy: the great social reformer of modern India
Keywords: India-History